Sistem Informasi Perhitungan Prioritas Pembangunan Daerah (SIPETAS) Berbasis Website - Deddy Supriadi; Linda Nurmala; Hasan Basri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2022)
Development in all sectors is needed, especially by a country that is classified as a developing country like Indonesia. In carrying out development, each local government requires development planning with the aim that each development has an accurate impact and can evaluate what is being built. Regional development planning must also pay attention to the priorities of the development plan to be planned, so that regional development planning is in accordance with what is needed by the region. The purpose of this study is to create a website-based information system design regarding prioritizing regional development planning because the system currently running at BAPPEDA Ciamis district still uses a manual system and has not yet used a decision support system so that the process of determining regional development planning priorities experiences many obstacles, starting from the lack of data needed makes it difficult to determine regional development planning priorities. The method used in this study is the promethee method which includes the Decision Support System for ranking an object. The results of this study are the creation of a website-based information system design using a decision support system for calculating the promethee method. In addition, by using a website-based information system, requests for development plans proposed by the sub-district are more effective and efficient.